Redox Balance in β-Thalassemia and Sickle Cell Disease: A Love and Hate Relationship - Rayan Bou-Fakhredin; Lucia De Franceschi; Irene Motta; Assaad A. Eid; Ali T. Taher; Maria Domenica Cappellini (MDPI AG, 2022)
β-thalassemia and sickle cell disease (SCD) are inherited hemoglobinopathies that result in both quantitative and qualitative variations in the β-globin chain. These in turn lead to instability in the generated hemoglobin (Hb) or to a globin chain imbalance that affects the oxidative environment both intracellularly and extracellularly. While oxidative stress is not among the primary etiologies of β-thalassemia and SCD, it plays a significant role in the pathogenesis of these diseases. Different mechanisms exist behind the development of oxidative stress; the result of which is cytotoxicity, causing the oxidation of cellular components that can eventually lead to cell death and organ damage. In this review, we summarize the mechanisms of oxidative stress development in β-thalassemia and SCD and describe the current and potential antioxidant therapeutic strategies. Finally, we discuss the role of targeted therapy in achieving an optimal redox balance.